Critical indices of the ferroelectric phase transition in TGS crystals - Myshchyshyn, O.; Andriyevsky, B.; Romanyuk, M. (Condensed Matter Physics, 1999)
Temperature dependencies of retardation, electron susceptibility and linear thermal expansion for three crystal-physic directions are obtained by means of optical investigations of the ferroelectric phase transition in TGS crystal using the James-type interferometer. Temperature dependencies of the spontaneous changes of the characteristics studied in the 39–49◦ C range are ﬁtted by the power low Y ~ τ²β with double critical indices 2β=0.87–0.95. Difference of 2β values from the unity is explained by the essential temperature dependence in the range close to the phase transition point for the coefﬁcients of electrooptic, reversed piezoelectric and electrostriction effects. Шляхом оптичних вимірювань сегнетоелектричного фазового переходу в кристалі тригліцинсульфату за допомогою інтерферометра Жамена одержано температурні залежності оптичної рiзниці ходу, електронної сприйнятливості та лінійного розширення для трьох кристалофізичних напрямків. Температурні залежності спонтанних змін досліджуваних характеристик в області 39–49◦ C апроксимовані степеневими залежностями Y ~ τ²β з подвійними критичними індексами 2β=0.87–0.95. Відмінність 2β від одиниці пояснюється суттєвою температурною залежністю поблизу точки фазового переходу коефіцієнтів електрооптичного, оберненого п’єзоелектричного ефектів та електрострикції.